DEVELOPMENT OF ASSESSMENT INSTRUMENTS FOR THE INTRODUCTION OF EARLY CHILDHOOD GEOMETRY FORMS IN THE INDEPENDENT CURRICULUM : PENGEMBANGAN INSTRUMEN PENILAIAN PENGENALAN BENTUK GEOMETRI ANAK USIA DINI DALAM KURIKULUM MANDIRI - Shofa; Rivo Panji Yudha (Jurnal Riset Golden Age PAUD UHO, 2025)
This research aims to develop performance assessment instruments to evaluate preschool children's ability to recognize geometry. The research methodology uses a Research and Development (R&D) approach with the 4-D model developed by Thiagarajan and collaborators, which includes the Define, Design, Develop, and Disseminate stages. The research was conducted at TK Cahyani and involved 10 children aged 5-6 for a small-scale test. In the Define stage, the research began with a field needs analysis and literature study. The Design stage focused on producing an initial product or prototype of the performance assessment design, including the grid, task assignment design, and assessment rubric. The development of the instrument was based on a systematic approach that involved curriculum and material analysis. The Develop stage involved creating the product based on the designed plan, considering validity, reliability, and effectiveness. The research results showed that the developed assessment instrument met the criteria for validity and reliability, suitable for use in teaching geometry to preschool children. The instrument is designed to be attractive and fun, motivating children to learn geometry through group activities and projects that require the application of geometric shapes in real-life situations.